Household Food Security: Evaluation of Influential Variables Using Exploratory Factor Analysis - Irwansyah, Budi; Puji Lestari, Lilla; Darmayani, Satya; Nilna Minah, Faidliyah; Jelita, Jelita (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2024)
Understanding the patterns that influence food security is very important. Deconstructing food security assessment into clearly defined variables might enhance its effectiveness. Efforts to improve food security measurements are generally prioritized on the most visible, objectively measurable, and familiar dimensions. In reality, there is sometimes confusion regarding which components of the food security definition a metrics is assessing, leading to the interchangeable use of indicators for distinct food security dimensions. Identifying, studying, and understanding these determining factors is the first step in exploring government policies and strategies to reduce food insecurity in any development. This research aims to analyze and identify those factors that have been identified through literature, their ranking is done by a questionnaire-based survey and an exploratory factor analysis approach. The literature identifies fifteen variables that have an impact on family food security. From these variables, four elements are extracted, which are household debt, distance to market, age of household head, and transportation cost dimensions. The findings of this study can serve as a point of reference for future research aiming to understand the impact of these four characteristics on family food security.